Step-by-Step Studio : Drawing Concepts - Goldman, Ken; Powell, William; Cardaci, Diane; Rosinski, Carol (Walter Foster, 2021)
With easy-to-follow, in-depth instruction from four accomplished artists, Step-by-Step Studio: Drawing Concepts teaches the foundational skills beginning artists need to get started with graphite pencil.